If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2 + w) + -4w = 3w + -10 (2 * 3 + w * 3) + -4w = 3w + -10 (6 + 3w) + -4w = 3w + -10 Combine like terms: 3w + -4w = -1w 6 + -1w = 3w + -10 Reorder the terms: 6 + -1w = -10 + 3w Solving 6 + -1w = -10 + 3w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3w' to each side of the equation. 6 + -1w + -3w = -10 + 3w + -3w Combine like terms: -1w + -3w = -4w 6 + -4w = -10 + 3w + -3w Combine like terms: 3w + -3w = 0 6 + -4w = -10 + 0 6 + -4w = -10 Add '-6' to each side of the equation. 6 + -6 + -4w = -10 + -6 Combine like terms: 6 + -6 = 0 0 + -4w = -10 + -6 -4w = -10 + -6 Combine like terms: -10 + -6 = -16 -4w = -16 Divide each side by '-4'. w = 4 Simplifying w = 4
| -2=7-x | | 2-(x-3)=4x+15 | | -4=7-x | | -6=7-x | | f(x)=2x^2+3x+6 | | 4=2-4x | | 0=2-4x | | 5x+19=2x+31 | | 8m-2(3m+3)=-5+2m-1 | | 4a+8=14-2(3-2a) | | 230+0.25x=425 | | 230+0.25=425 | | 3x^2-16x-2=-7 | | 5y-7-3y=19 | | -6=3x-8 | | 8p+2=4p-1 | | -3=3x-8 | | 2(x-3)+4=8x-5-6x | | 1=3x-8 | | 2x-kx=3 | | 345.43=170+0.83x | | 4+5x=45 | | -8x-10+4x=14 | | 10.8x-3.7x=127.8 | | 15y-10y=20 | | (8b+7)(10b-2)=0 | | 44x+9=3 | | 15y=10x | | 15-6+4= | | 8y-6y=6 | | 4(3-x)=-2(x-1) | | 3t-7=7 |